Operational and Policy-Related Data Assessment and Recommendations from Review-based Analysis of Autonomous Shuttle Deployments - Diba, Dil Samina; Pulugurtha, Srinivas (Transportation Development Research, 2024)
The advent of driverless technology and supporting infrastructure has enabled the implementation of autonomous shuttles for enhancing mobility and providing first and last-mile (F & LM) connectivity. These shuttles have been employed to address short-distance travel needs, serve internal transportation needs, and cater to specific use cases, such as recreational parks, business parks, and university campuses. Successful deployment of autonomous shuttles depends on the service location and the target customer base. Factors such as capacity, speed, incidents/crashes, comfort, and road characteristics influence their successful integration into the transportation system. Practitioners can better plan future deployments by learning from past and current autonomous shuttle deployments and their documented outcomes. This study compares the operational and policy-related data from 120 autonomous shuttle deployments worldwide. Additionally, a review-based analysis was conducted to identify the strengths, weaknesses, opportunities, and threats associated with autonomous shuttle deployments. Recommendations for future deployments are made emphasizing the need for longer trial periods and the development of a comprehensive policy framework.